Developing Reading Material for Elementary Students in Tourism Area by Inserting Local Culture - Kusuma, I Putu Indra (JEELS (Journal of English Education and Linguistics Studies), 2016)
This research and development (R&D) aimed at 1) developing reading material for the fifth grade students of elementary schools in tourism area, and (2) investigating the quality of the material developed. To gather the data, this study used scoring rubric, questionnaires, observation sheets, interview guide, and test. This study used the development model proposed by Sugiyono (2011) and was developed based on the characteristics of good reading material proposed by Tomlinson (1998). The results showed that (1) reading material was developed by involving some of local contents and (2) reading material had high validity and practicality and was proven to be effective. It then can be concluded that to make good quality of a reading material, the development of it should involve local content and should be based on the criteria of good material.